A reduced-order model applied to the 2D shallow water equations - Solán Fustero, Pablo; Gracia, José Luis; Navas Montilla, Adrián; García-Navarro, PIlar (Jornada de Jóvenes Investigadores del I3A, 2022)
The numerical resolution of shallow water equations (SWE) is required in many environmental problems involving free surface flow. Reduced-order models (ROMs) based on the POD allow such problems to be solved more efficiently in terms of computational cost without losing accuracy, as discussed in this work.